Determine the Impact of Nanoscale Zinc Oxide Particle on Growth, Yield and Soil Properties under Agency Area of Andhra Pradesh, India - P. Venkata Ramana; T. N. K. V. Prasad; Sandeep Naik; Ch. Apparao (Emerging Issues in Agricultural Sciences Vol. 3, 2023)
The present study was carried out to investigate the effects of various concentrations of Zinc Oxide (ZnO) NPs on growth, yield and grain Zn content in groundnut. Zinc is an essential micronutrient for humans, animals and plants. Higher plants generally absorb Zn as a divalent cation (Zn+2), which acts either as the metal component of enzymes or as a functional structural or a regulatory co-factor of a large number of enzymes. Field experiment was carried out on silt clay loam soils at Regional Agricultural Research station, Chintapalle, Visakhapatnam, Andhra Pradesh during 2018-2020 to study the yield of response of rainfed groundnut with different levels of Nano particulate zinc oxide application along with NPK Fertilizers. The experiment consisting of eight treatments, three replications with RDF design. Results of nano particulate zinc oxide on pod yield showed that (26.34 Q/ha) in the RDF+ nano scale zinc oxide level @ 200 ppm at 25 and 45 DAS was increased over to that of normal recommended dose of N,P,K fertilizers (100% RDF) which recorded pod yield of 17.14 Q/ha only. Application of ZnSO4 through soil along with RDF showed good results (17.24 Q/ha) than RDF + Foliar application of ZnSO4 @ 2g/lit at 25 and 45 DAS (20.66 Q/ha). Application of micronutrient (ZnO) had helped in further increase in grain yields at both levels of ZnO (150% and 200% ZnO at 25 and 45 DAS). Among different treatments, significantly higher yield (26.34 Q/ha) was recorded with application of RDF + Foliar application of ZnO @ 200 ppm at 25 and 45 DAS than the only with RDF (17.4 Q/ha). With respect to method of application of ZnSO4 through soil and foliar application ZnSO4 @ 2g/lit at 25 and 45 DAS was found to be higher both levels of RDF (Pod yield of 14.6 Q/ha at RDF + Soil application of ZnSO4 @ 50 kg ha-1 and 17.24 Q/ha at RDF+ foliar application of ZnSO4@ 2g/lit at 25 and 45 DAS). With respect to other plant characteristics, comparitavely more plant height (37.6 cm) at RDF + foliar application of ZnO @ 200 ppm at 25 and 45 DAS. Regarding yield attributes significantly higher test weight (30.9 g) and plant dry weight (273 g per plant) were recorded at RDF + 150 ppm ZnO at 25 and 45 DAS. Post –harvest soil sample analysis showed highest availability of nutrients in respect of soil, the results revealed that there was no significance difference among the treatments regarding Avail. N, Available K and pH. The lowest Phosphorus (17.20 kg ha-1) was recorded with RDF+ Foliar application of nanoscale ZnO 200ppm at 25 & 45 DAS and highest (24.46 kg ha-1) was recorded in T9 (RDF+ Foliar application of nanoscale ZnO 100 ppm at 25 & 45 DAS). The results point to the use of nanoscalematerials in agriculture, especially in peanut, one of the main source of livelihood in certain parts of the world. The results emphasized that nanoscale nutrients can be supplied to the crops either through seed dressing or by foliar application with much decreased doses to get the desired results. The bio availability of the nanoparticles because of its size and lower water solubility (which inhibit rapid falling off compared to ionic supplements) can also be highesr compared to ZnSO4. The inherent small size and the associated large surface area of nanoscale ZnO fertilizer may increase the uptake as reported earlier.